Less Stress, More Satisfaction with Online Learning During the COVID-19 Pandemic: The Moderating Role of Academic Resilience - Kumalasari, Dewi; Akmal, Sari Zakiah (Psychological Research on Urban Society, 2021)
The COVID-19 outbreak triggered a sudden transformation in all aspects of life. Inevitably, educational environments were also affected. Previous studies found a sharp drop in student satisfaction and a simultaneous corresponding increase in academic stress when online learning was instituted due to the pandemic. Conversely, academic resilience is considered psychological capital; it enables students to overcome stress and stimulates satisfaction. The interactions of these three variables must thus be collectively examined. This study used the convenience sampling technique to investigate the moderating role of academic resilience vis-à-vis academic stress and student satisfaction with online learning during the COVID-19 pandemic. Data were collected via an online questionnaire from a sample of 337 Indonesian undergraduate students aged 18‒32 years recruited for this study. The questionnaire encompassed three measurement instruments: Stressor Scale for College Students (α =.85), Academic Resilience Scale-Indonesian version (α =.89), and Student Satisfaction with Online Learning (α =.90). Linear regression analysis revealed that academic stress exerted a significant negative effect on satisfaction with online learning. Academic resilience was a significant moderator, dampening the effects of academic stress on satisfaction with online learning. The theoretical and practical implications of the research results are also discussed.